Prenatal Genetic Screening and Diagnostic Testing: Assessing Patients' Knowledge, Clinical Experiences, and Utilized Resources in Comparison to Provider's Perceptions - Delgado, Arlin; Schulkin, Jay; Macri, Charles J. (American Journal of Perinatology Reports, 2022)
Objective This survey study aimed to assess patient knowledge, clinical resources, and utilized resources about genetic screening and diagnostic testing.Study Design A one-time anonymous paper survey was distributed to 500 patients at a major urban obstetrics and gynecology department, and an online survey was sent to 229 providers. Descriptive statistics and chi-squared analyses were performed.Results In all, 466 of 500 patient surveys were completed, and 441 analyzed (88.2% response rate). Among providers, 66 of 229 (29.0% response rate) responded. Patients were on average 32 years old, 27 weeks pregnant, and most often reported a graduate degree level of education (47.4%). Over 75% of patients reported accurate knowledge of basic genetic statements. Patients reported that discussing screening and diagnostic testing with their provider was significantly associated with properly defining screening and diagnostic testing (p < 0.001). Less than 10% of patients reported providers distributing web/video links, books, or any other resource; however, patients most often independently accessed web links (40.1%).Conclusion Our findings suggest a positive impact from patient and provider discussions in office on patient knowledge and understanding. Discrepancies between educational resources distributed in the clinic and individually accessed resources highlight possible areas of change. Future work should evaluate and implement differing resources to increase patient knowledge.
Keywords: patient–provider communication; pregnancy related care; genetic counseling; genetic screening; genetic testing